Endometriosis: time to think differently (and together) - Dixon, S; Mawson, R; Kirk, UB; Horne, AW (Royal College of General Practitioners, 2024)
Endometriosis affects approximately 10% of people assigned female at birth, an estimated 190 million women worldwide. At an individual level, endometriosis can be asymptomatic, or can cause a spectrum of chronic pain, fatigue, bowel and bladder symptoms, depression, and other comorbidities, including infertility. A challenge for clinicians, perhaps notably in general practice, is that endometriosis is markedly heterogeneous, with no predictable correlation between symptoms experienced and the extent of endometriosis identified during diagnostic laparoscopy or on imaging. Likewise, endometriosis-associated pain can persist when visibly apparent endometriosis is treated. Economically, the annual accumulated cost of endometriosis is estimated to be £12.5 billion in the UK, including treatment, health care, loss of productivity, and absence from work. Endometriosis has significant potential adverse impacts on an individual’s quality of life. On average, sufferers lose up to 11 hours of work per week due to endometriosis symptoms, a figure similar to chronic conditions such as type 2 diabetes, Crohn’s disease, and rheumatoid arthritis.